Water rights and water trading in England and Wales - Stern, J (2013)
This policy brief discusses the role of ‘rights’ in water use and water trade in the context of climate change. Abstraction rights and their ownership are related to water ‘commons’ and traditional riparian rights. When the demand for water (including water for the environment) exceeds the available supply in some regions, there is a need to encourage trade both in water licence rights and in bulk water. This position has been reached in England and Wales and the problems are likely to increase in coming years and decades. The policy brief presents the implications of this for the definition and operation of property rights in water, including options for abstraction licence reform. The policy brief concludes with a discussion of a model which redefines water abstraction rights in terms of percentage shares of available water rather than in physical units. The ‘water shares’ approach to water pricing and trade has become arguably the leading option for abstraction reform. An abstraction mechanism of this type can make a major contribution to commodifying the use of water while ensuring sufficient water for ‘the environment’. By providing secure property rights and ensuring that trade reflects security, water rights and water trading are not just reconciled but can reinforce one another.